Pulmonary inhalation performance of chitosan nanoparticles admixed with lactose-poly ethylene glycol microparticles / Nasser Ahmed Mohammed Al Hajj - Mohammed Al Hajj, Nasser Ahmed (2016)
Nanoparticles are characterized by poor pulmonary inhalation performance as they are exhalation prone, in addition to their tendency to form agglomeration due to large surface area to volume ratio thereby hindering their deep lung deposition. Coarse carriers commonly used in dry powder inhaler cannot be used to deliver nanoparticles to the lung. The nanoparticles will be attach strongly to them and deposit in the throat, or they will detach, enter the lung and be exhaled. This study aimed to develop a platform where the nanoparticles were distributed over the microparticles for pulmonary delivery of nanoparticulate system.